Contrast Dye ICE Cap Embolization Using the Third‐Generation Cryoballoon. Issue 2 (10th November 2016) - CONTI, SERGIO; MOLTRASIO, MASSIMO; TONDO, CLAUDIO; FASSINI, GAETANO
Abstract : Cryoballoon ablation is a widely diffuse technology to perform paroxysmal atrial fibrillation ablation. The new generation cryoballoon catheters have been redesigned in order to improve the cooling capability. During cryoballoon ablation, it is not unusual to observe the formation of a contrast dye ice cap on top of the balloon itself. The automated balloon deflation before dissolution of the ice cap may increase the risk of embolization of large ice‐mixed‐contrast crystals in the systemic circulation. In the case hereby reported, we describe an uneventful embolization of this contrast dye ice cap in the systemic circulation.